Analisis Perbandingan Kinerja Pemerintah Daerah sebelum dan saat Pandemi Covid-19 - Muhammad Hamdan Sayadi; Muhammad Bahrul Ulum; Rafika Sari (Jurnal Akuntansi dan Pajak, 2023)
Local government financial statements can be used to measure the financial performance of a region whether it is classified as good or bad. This study aims to analyze and describe the performance of local governments in Sumatra using the ratio of regional financial dependence levels before and during the Covid-19 pandemic. This research is classified as a quantitative descriptive method and uses regional financial dependency ratios as an analytical tool. The results of research on the comparison of financial performance between 10 provinces on the island of Sumatra in 2019 and 2020 show that the financial performance of provinces located on the island of Sumatra has a very high financial dependence on the central government. The level of dependence has increased during the COVID-19 pandemic. The results of the analysis show that Aceh province with the best financial performance during the pandemic period is based on the regional financial dependence ratio with a ratio of 28.49%. The highest regional financial dependency ratio is in the Riau Islands province with a ratio of 65.39%. Further research is expected to expand and expand the research sample and use other indicators in analyzing the financial performance of local governments.